2021
DOI: 10.3390/jcm10245756
|View full text |Cite
|
Sign up to set email alerts
|

Retinal and Choriocapillary Vascular Changes in Early Stages of Multiple Sclerosis: A Prospective Study

Abstract: Optical Coherence Tomography Angiography (OCTA) abnormalities occur in multiple sclerosis (MS) over the course of the disease. OCTA investigations at early MS stages are lacking. We aimed to investigate vessel density in macular and papillary regions over two years after an initial demyelinating event (IDE). Vessel density was analyzed in superficial, deep, choriocapillaris and radial peripapillary plexus at baseline, and after one and two years. We also evaluated structural OCT parameter changes of the gangli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
1
10
1
Order By: Relevance
“…Therefore, we combined these results into a single study. Ultimately, this meta-analysis included 13 studies with 996 MS eyes and 847 HC eyes (Lanzillo et al, 2018;Feucht et al, 2019;Cennamo et al, 2020;Cordon et al, 2020;Farci et al, 2020;Murphy et al, 2020;Ulusoy et al, 2020;Yilmaz et al, 2020;Aly et al, 2021;Kallab et al, 2021;Khader et al, 2021;Montorio et al, 2021;Rogaczewska et al, 2021a,b). Murphy et al (2020) reported the results…”
Section: Included Studies and Main Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, we combined these results into a single study. Ultimately, this meta-analysis included 13 studies with 996 MS eyes and 847 HC eyes (Lanzillo et al, 2018;Feucht et al, 2019;Cennamo et al, 2020;Cordon et al, 2020;Farci et al, 2020;Murphy et al, 2020;Ulusoy et al, 2020;Yilmaz et al, 2020;Aly et al, 2021;Kallab et al, 2021;Khader et al, 2021;Montorio et al, 2021;Rogaczewska et al, 2021a,b). Murphy et al (2020) reported the results…”
Section: Included Studies and Main Characteristicsmentioning
confidence: 99%
“…stratified by image artifact grading, and we only included the data of minimal artifact in the quantitative analysis of meta-analysis. Among 13 included studies, four studies (Cordon et al, 2020;Farci et al, 2020;Kallab et al, 2021;Khader et al, 2021) analyzed monocular data, whereas nine studies (Lanzillo et al, 2018;Feucht et al, 2019;Cennamo et al, 2020;Murphy et al, 2020;Ulusoy et al, 2020;Yilmaz et al, 2020;Aly et al, 2021;Montorio et al, 2021;Rogaczewska et al, 2021a,b) analyzed biocular data. For patients with MS, the mean illness duration ranged from 4 to 11 years and the mean EDSS scores ranged from 1.0 to 3.5.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Studies have also identified OCT-A as a potential tool for monitoring disease progression. Recent data suggest that marked vascular loss in the SVP, DVP, and pRPC may be observed in people with an initial demyelinating event, although no changes might occur in the RNFL, GC-IPL thickness, or clinical and radiological examinations [ 59 ].…”
Section: Optical Coherence Tomography With Angiography In Multiple Sc...mentioning
confidence: 99%